Membangun Kampus Merdeka: Mencegah dan Mengatasi Kekerasan Seksual di Lingkungan Perguruan Tinggi - Teresia Eka Maulinda; Masduki Asbari; Selly Selviana (AGUSPATI RESEARCH INSTITUTA, 2024)
Sexual violence is unwanted sexual activity, either verbally or in action. With the issuance of Minister of Education and Culture Regulation Number 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments, the sanctions regulated lead to administrative sanctions. Higher education leaders are not part of investigators, investigators, public prosecutors, or a panel of judges who can represent the state in carrying out the criminal process. The approach used in this study is a descriptive qualitative approach. Qualitative research is research that produces descriptive data, namely observing the speech or writing and behavior of the people being observed. According to the observed context, the data obtained is then recorded and analyzed. The method used in this research is the listening method because the data source is obtained by listening to language use. The data source that was viewed was the Indonesian Ministry of Education and Culture's video with the title